Optimization of Fe-Cr-Mn alloy composition as implant material for mechanical properties and corrosion resistance - Kartikasari, Ratna; Kadiman, Sugiarto; Muhfidin, Rivan; Aziz, Ihwanul (Eastern-European Journal of Enterprise Technologies, 2025)
The object of this study is Fe-Cr-Mn stainless steel alloys containing 0.23–0.41 wt.% C and 17.59–18.36 wt.% Cr with varying Mn content. The development of nickel-free stainless steels addresses the drawbacks of conventional implant materials such as titanium alloys, Co-Cr alloys, and AISI 316L stainless steel, which often suffer from biocompatibility issues, toxicity, and mechanical incompatibility with bone. The Fe-Cr-Mn alloys were produced by high-frequency induction melting and subsequently tested for microstructure, mechanical, wear, and corrosion properties. SEM-EDS revealed a transition from ferritic structure (2.5% Mn) to duplex α+γ (5% Mn) and predominantly austenitic structure (7.5% Mn). Mechanical testing showed that hardness and tensile strength peaked at 2.5% Mn, while ductility and impact toughness improved with increasing Mn, reaching their highest values at 5% Mn. Wear resistance increased significantly at higher Mn levels due to the formation of stable tribo-oxides and the strengthening effect of the austenitic matrix. Electrochemical testing in 0.9% NaCl solution showed that Fe-18Cr-5Mn possessed the best corrosion resistance, attributed to the stability of its passive film, while excessive Mn (7.5%) caused passivation breakdown through Mn-hydroxide formation. Overall, Fe-18Cr-5Mn exhibited the best synergy between strength, toughness, wear resistance, and corrosion protection under physiological saline conditions, establishing it as a promising nickel-free stainless steel for next-generation biomedical implant materials